Institutional reflections on firm's corporate sustainability practices: Case All Nippon Airways - Riionheimo, Sara Linnea (My University, 2023)
Companies are facing pressure to acknowledge their influence on the environment and surrounding communities. Thus, corporate sustainability practices are becoming an important part of companies’ strategies. The pressures and drivers for companies to engage in sustainable practices have been immensely studied. However, there is a gap in research of the institutional pressures on corporate sustainability. The purpose of this study is to explore how formal and informal institutional pressures influence a company’s corporate sustainability practices. This study has specifically focused on an aviation company to study institutional pressures from national, industry and global levels. The literature review of this study is combined of two key theories: the triple bottom line and institutional theory. Corporate sustainability practices are discussed based on the triple bottom-line framework. The triple bottom-line divides corporate sustainability into economic, environmental, and social dimensions. Institutional theory on the other hand is a theory that assumes organizations conform to their surrounding institutions. Institutions can be divided into formal and informal. Formal institutions refer to regulations and policies whereas informal institutions refer to norms, values, and beliefs. The regulations, norms and culture of an organization’s environment influence its’ decisions and the outcomes of those decisions. Institutions are also found to influence different sustainability aspects. This study was made as a case study on a Japanese aviation company All Nippon Airways. For this study the author has chosen a qualitative method and an abductive approach. The thesis is based on secondary data which has been carefully chosen to create a reliable understanding of case company’s corporate sustainability practices and institutional environment. The case company’s corporate sustainability practices where analyzed and corporate sustainability themes were created based on the analysis. Secondary data was gathered from multiple sources to understand the regulations, policies, norms, cultural values and beliefs affecting the company. The findings of this study are in line with previous studies and show that institutional pressures do influence company’s corporate sustainability practices. Both formal and informal institutions were found to influence all dimensions of corporate sustainability. Specifically informal institutional pressures were found to influence the social sustainability dimension. Economic sustainability was the least affected by institutional pressures which could indicate a more internal motivation for economic sustainability. Informal institutional pressures that were in line with sustainability values supported corporate sustainability practices beyond just regulatory compliance.

Yritykset kohtaavat yhä enemmän paineita ottaa vastuuta vaikutuksistaan ympäristöön ja yhteiskuntaan. Yritysten kestävyystoiminnot ovat tulleet tärkeäksi osaksi yritysten strategiaa. Tekijöitä, jotka kannustavat yrityksiä osallistumaan kestävyystoimintoihin on tutkittu jo laajasti. Yrityskestävyyden tutkimuksessa on kuitenkin vielä aukko instituutioiden vaikutuksissa yritysten kestävyystoimintoihin. Tämän tutkimuksen tavoitteena on tarkastella, miten viralliset ja epäviralliset instituutionaaliset paineet vaikuttavat yrityksen kestävyystoimintoihin. Tämä tutkimus keskittyy erityisesti ilmailualan yritykseen, jotta tutkimuksessa voidaan ottaa huomioon institutionaaliset paineet kansallisella, globaalilla ja alan tasolla. Tutkimuksen kirjallisuuskatsaus muodostuu kahdesta pääteoriasta: kolmoistilinpäätöksestä ja institutionaalisesta teoriasta. Yrityksen kestävyystoiminnoista puhutaan kolmoistilinpäätöksen mukaisesti. Kolmoistilinpäätöksen mukaan yrityskestävyys jaetaan taloudelliseen, ekologiseen ja sosiaaliseen ulottuvuuteen. Institutionaalinen teoria taas olettaa, että organisaatiot sopeutuvat niitä ympäröiviin instituutioihin. Instituutiot voidaan jakaa virallisiin ja epävirallisiin instituutioihin. Virallisilla instituutioilla tarkoitetaan pakottavia säädöksiä ja käytäntöjä, kun taas epävirallisilla instituutioilla tarkoitetaan normeja, arvoja ja uskomuksia. Organisaation toimintaympäristön säädökset, normit ja kulttuuri vaikuttavat sen päätöksiin ja niiden päätösten lopputulemiin. Instituutiot vaikuttavat myös erilaisiin kestävyyden puoliin. Tämä tutkimus on tehty tapaustutkimuksena japanilaisesta lentoalan yrityksestä All Nippon Airwaysistä. Tutkimuksen tavoitteen mukaisesti metodologiaksi on valittu laadullinen tutkimus ja tutkimuksessa hyödynnetään abduktiivista päättelyä. Tutkimus perustuu sekundääriseen dataan, joka on valikoitu tarkasti luomaan luotettava ymmärrys yrityksen kestävyystoiminnoista ja institutionaalisesta ympäristöstä. Yrityksen kestävyystoiminnot on analysoitu ja analyysin perusteella luotiin yrityskestävyyden teemat. Sekundääridataa kerättiin useammista lähteistä luomaan kattava kuva virallisista säännöksistä, käytänteistä, normeista, kulttuurisista arvoista ja uskomuksista. Tämä tutkimuksen löydökset vastaavat aikaisempia tutkimuksia ja osoittavat, että institutionaaliset paineet vaikuttavat yrityksen kestävyystoimintoihin. Tutkimuksen mukaan sekä viralliset että epäviralliset instituutiot vaikuttivat jokaiseen kestävyyden ulottuvuuteen. Erityisesti epäviralliset instituutiot vaikuttivat sosiaaliseen kestävyyteen. Ekonomiseen kestävyyteen institutionaaliset paineet vaikuttivat vähiten, mikä saattaa viitata siihen, että yrityksen sisäiset motivaatiot vaikuttavat enemmän tähän kestävyyden ulottuvuuteen. Epäviralliset instituutiot, jotka vastasivat kestävyyden mukaisia arvoja, tukivat yrityksen kestävyystoimintoja vain virallisten määräysten noudattamista pidemmälle.
Keywords: sustainable development; institutionalisation (societal change); corporate responsibility; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business